2000
DOI: 10.1086/309526
|View full text |Cite
|
Sign up to set email alerts
|

An Interesting Episode of Accretion Activity in UX Orionis

Abstract: This paper presents observations of an episode of accretion activity in the preÈmain-sequence star UX Ori. High-velocity, redshifted absorption is seen in several lines of H, Ca II, Na I, and Fe II during an interval of eight nights in the fall of 1996 with similar velocity and time evolution. A non-LTE analysis of the line optical depths shows that the infalling gas cannot be heavily hydrogen-depleted, as would be expected if it was produced by the evaporation of a solid body of chemical composition similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 17 publications
4
38
0
Order By: Relevance
“…The structure and parameters of the magnetosphere in HAEBEs are still not fully understood. Natta et al (2000) presented direct evidence of the gas infall in HAEs. Using a non-LTE analysis of the line optical depths, they showed that the infalling gas cannot be heavily hydrogen depleted, which suggests a similarity between HAEs and classical T Tauri stars, where gas infall occurs in an analogous fashion.…”
Section: Hybrid Model: Disk Wind X-wind and Magnetospherementioning
confidence: 99%
“…The structure and parameters of the magnetosphere in HAEBEs are still not fully understood. Natta et al (2000) presented direct evidence of the gas infall in HAEs. Using a non-LTE analysis of the line optical depths, they showed that the infalling gas cannot be heavily hydrogen depleted, which suggests a similarity between HAEs and classical T Tauri stars, where gas infall occurs in an analogous fashion.…”
Section: Hybrid Model: Disk Wind X-wind and Magnetospherementioning
confidence: 99%
“…Thus, the analysis of the CS contribution to the observed spectra requires a careful subtraction of the stellar photospheric spectrum and a method to characterize the blended kinematical components. In this section we describe the procedure we have followed, which is the one used in Natta et al (2000), although we have improved it by considering all detected TACs simultaneously.…”
Section: Analysis Of the Spectramentioning
confidence: 99%
“…As a more convenient way to represent this contribution we define the R parameter (normalized residual absorption): R = 1 − F obs /F syn R = 0 means no CS absorption, and R = 1 denotes complete stellar light occultation, i.e. R quantifies the CS absorption strength and could be directly compared to the models in Natta et al (2000). R is also plotted in Fig.…”
Section: Subtraction Of the Ux Ori Photospheric Spectrummentioning
confidence: 99%
See 2 more Smart Citations